KELAYAKAN USAHATANI BAWANG DAUN (Allium fistulosum) DI DESA PINANG HABANG KECAMATAN WANARAYA KABUPATEN BARITO KUALA KALIMANTAN SELATAN - Mega Silvia; Suslinawati Suslinawati; Gusti Khairun Ni'mah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
The research was conducted in the village of Pinang Habang Wanaraya Barito Kuala District of South Kalimantan Province. When the study began in October until April. Data collected includes primary and secondary data by using a sampling technique by means of a simple random sample (Sample Random Sampling) is sampling 25% of the 87 farmers as many as 22 people are to farm the farmer scallion scallion. The results showed that the production of scallions average of 3545.45 kg / one growing season with an average land area of 0.30 ha / farmer. The amount of revenue that an average of Rp39.000.000,00, - the selling price Rp11.000,00, - / kg. The total average cost of Rp21.330.847,36, - / farmers include explicit costs an average of Rp9.240.732,85, - / farmers and implicit costs an average of Rp21.004.166,66, - / farmers. so that the total average cost of Rp30.244.899,51, - / farmers. While the average income of Rp29.759.267,15, - / farmer with a gain of Rp8.755.100,49, - / farmers. Feasibility level with RCR value of 1.29 and, -, with a breakeven point BEP Production amounted to 369.69 kg less than the amount of production that is equal to 3545.45 kg, and the price of Rp8.548,54 BEP, - less than the price the current Law Rp11.000,00, -, scallion kg, the farmers gain acceptance for Rp4.066.553,15, -. means farming leek Pinang Village Habang Wanaraya Barito Kuala District of South Kalimantan worth the effort.